Antibacterial mildew-proof glue and preparation method thereof
By adding glass-based silver-zinc composite antibacterial agent and nano sustained release antibacterial agent to the polyvinyl alcohol adhesive, combined with organic-inorganic composite emulsion and modified silica sol, the problems of poor antibacterial and poor water resistance of polyvinyl alcohol adhesive are solved, and better antibacterial and anti-mold effect and adhesive properties are achieved.
Patent Information
- Application Number
- CN202411785070.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
As an adhesive, polyvinyl alcohol has problems such as poor antibacterial properties, poor water resistance and great brittleness, which affects the overall performance of paper products.
An antibacterial antibacterial gel is prepared by using glass-based silver-zinc composite antibacterial agent and nano sustained release antibacterial agent, combined with organic-inorganic composite emulsion, modified silica sol and catalyst.
This adhesive has good effects in antibacterial and anti-mold. By destroying the cellular structure of mold and bacteria, interfering with their metabolic process, prolonging the anti-mold effect, and improving the tensile strength and corrosion resistance of the adhesive.
Smart Images

Figure BDA0005173804590000071 
Figure BDA0005173804590000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmentally friendly adhesives, and more specifically, to an antibacterial and mildew-proof adhesive and a preparation method thereof. Background Art
[0002] The health risks brought by harmful microbial contamination such as bacteria, viruses, and fungi cannot be ignored, so antibacterial and anti-mildew technology is one of the important means to protect health. In recent years, antibacterial and anti-mildew materials have been widely used in medical devices, home appliances, food packaging, architectural coatings, textiles and other fields to improve the living environment, reduce the risk of public cross-contamination or extend the service life of materials.
[0003] The development of modern science and technology requires adhesives to not only be able to bond various materials, but also put forward various special requirements for bonding performance and process. Fillers can also be added to adhesives to increase hardness, modulus, improve the mechanical properties of bonding, etc., and can be used in the processing of various paper products to improve the strength, smoothness, sealing and waterproofness of paper products. With the extensive use of secondary fibers, people have higher and higher requirements for the strength of paper products, resulting in increasing dependence on adhesives. Among them, polyvinyl alcohol is a high-molecular organic compound prepared by saponification reaction. The molecular chain contains a large number of hydroxyl groups. The material made has excellent physical strength, excellent degradability, non-toxicity and harmlessness. It is an adhesive with excellent performance. However, polyvinyl alcohol contains a large number of hydroxyl groups, which can react with mold, resulting in poor antibacterial properties, poor water resistance, and high brittleness, which will affect the comprehensive performance of paper products. Summary of the invention
[0004] The invention provides an antibacterial and mildew-proof glue and a preparation method thereof. The prepared antibacterial and mildew-proof glue has good antibacterial and mildew-proof effects. The glass-based silver-zinc composite antibacterial agent added to the mildew-proof glue destroys the cell structure of molds and bacteria and interferes with their metabolic process, thereby achieving the antibacterial and mildew-proof effects.
[0005] In a first aspect, the present invention provides an antibacterial and mildew-proof glue, comprising the following components by weight: 15-20 parts of an organic-inorganic composite emulsion, 8-12 parts of a modified silica sol, 12-25 parts of a glass-based silver-zinc composite antibacterial agent, 0.6-2 parts of a nano slow-release mildew-proof agent, 0.01-2 parts of a catalyst, 22-40 parts of octyl isothiazolinone, 10-20 parts of a diisocyanate, and 5-15 parts of a hyperbranched polyamine.
[0006] Preferably, the composition comprises the following components by weight: 18-20 parts of organic-inorganic composite emulsion, 10-12 parts of modified silica sol, 15-20 parts of glass-based silver-zinc composite antibacterial agent, 0.6-1.5 parts of nano slow-release mildew preventer, 0.5-2 parts of catalyst, 22-32 parts of octyl isothiazolinone, 10-15 parts of diisocyanate, and 10-15 parts of hyperbranched polyamine.
[0007] Preferably, the composition comprises the following components by weight: 18-20 parts of organic-inorganic composite emulsion, 10-12 parts of modified silica sol, 18-20 parts of glass-based silver-zinc composite antibacterial agent, 0.9-1.2 parts of nano slow-release mildew preventer, 1.5-2 parts of catalyst, 26-30 parts of octyl isothiazolinone, 12-15 parts of diisocyanate, and 12-15 parts of hyperbranched polyamine.
[0008] Preferably, the composition comprises the following components by weight: 20 parts of organic-inorganic composite emulsion, 10 parts of modified silica sol, 15 parts of glass-based silver-zinc composite antibacterial agent, 0.8 parts of nano slow-release mildew preventer, 1.5 parts of catalyst, 30 parts of octyl isothiazolinone, 13 parts of diisocyanate, and 12 parts of hyperbranched polyamine.
[0009] Preferably, the organic-inorganic composite emulsion comprises a silane coupling agent, an active diluent, a modified nano-SiO 2 and epoxy resin, by modifying nano-SiO 2 The organic-inorganic composite emulsion is prepared by emulsifying epoxy resin and active diluent.
[0010] Preferably, the method for preparing the organic-inorganic composite emulsion comprises the following steps:
[0011] (1) Nano-SiO 2 , ethanol and aqueous solution are mixed and stirred evenly to obtain nano-SiO 2 Suspension;
[0012] (2) Add silane coupling agent to nano-SiO 2 The suspension is heated and stirred, and after centrifugation, washing and drying, the modified nano-SiO 2 ;
[0013] (3) Mix the epoxy resin and the active diluent and stir evenly, weigh the diluted epoxy resin and slowly add it to the modified nano-SiO 2 The suspension was stirred at 6000-8000 r / min for 30-50 min to obtain a composite emulsion.
[0014] Preferably, in step (3), the mass ratio of epoxy resin to reactive diluent is 1-4:1-3.
[0015] Preferably, in step (3), the mass ratio of epoxy resin to reactive diluent is 2:3.
[0016] Preferably, the modified silica sol is a water dispersion of surface-modified nano-silicon dioxide; the particle size of the modified silica sol is 5-12 nm, the pH is 8.0-10.0, and the mass content of non-volatile matter is 25-30%.
[0017] Preferably, the nano slow-release mildew inhibitor includes quaternary ammonium salts, organosilicon quaternary ammonium salts, guanidines, halogenated amine compounds, nano titanium dioxide and nano zinc oxide, and the mass ratio of the quaternary ammonium salts, organosilicon quaternary ammonium salts, guanidines, halogenated amine compounds, nano titanium dioxide and nano zinc oxide is 32-42:10-12:2-3:5-12:1-3:5-8.
[0018] Preferably, the nano slow-release mildew inhibitor includes quaternary ammonium salts, organosilicon quaternary ammonium salts, guanidines, halogenated amine compounds, nano titanium dioxide and nano zinc oxide, and the mass ratio of the quaternary ammonium salts, organosilicon quaternary ammonium salts, guanidines, halogenated amine compounds, nano titanium dioxide and nano zinc oxide is 32-36:7-12:2-3:5-8:1-3:5-8.
[0019] Preferably, the nano slow-release mildew inhibitor includes quaternary ammonium salts, organosilicon quaternary ammonium salts, guanidines, halogenated amine compounds, nano titanium dioxide and nano zinc oxide, and the mass ratio of the quaternary ammonium salts, organosilicon quaternary ammonium salts, guanidines, halogenated amine compounds, nano titanium dioxide and nano zinc oxide is 32:10:3:7:1:5.
[0020] Preferably, the catalyst is at least one of dibutyltin dilaurate, dibutyltin diacetate, dibutyltin dioctoate and a titanium chelate.
[0021] In a second aspect, the present invention provides a method for preparing an antibacterial and mildew-proof adhesive, comprising the following steps:
[0022] (1) uniformly mixing an organic-inorganic composite emulsion, a modified silica sol, octyl isothiazolinone, a diisocyanate and a hyperbranched polyamine to prepare a composition A;
[0023] (2) mixing a glass-based silver-zinc composite antibacterial agent, a nano slow-release mildew-proof agent and a catalyst to prepare a composition B;
[0024] (3) Mixing the composition A and the composition B and stirring them evenly to prepare an antibacterial and mildew-proof adhesive.
[0025] In a third aspect, the present invention provides an application of an antibacterial and mildew-proof adhesive in building interior materials.
[0026] In summary, the present invention has the following beneficial effects:
[0027] 1. The organic-inorganic composite emulsion of the present invention is a new type of material that combines the advantages of organic and inorganic substances. The addition of nanoparticles in the organic-inorganic composite emulsion plays the role of stress concentration points. When subjected to external forces, the nanoparticles will deform, thereby changing the physical structure of the adhesive and enhancing its tensile strength and corrosion resistance.
[0028] 2. The modified silica sol of the present invention has a large specific surface area and high stability, which can improve the compressive strength of the colloid. The nano slow-release mildew inhibitor is a material that uses nanotechnology to achieve mildew-proof effect. This mildew inhibitor wraps the mildew-proof component in nanomaterials to achieve slow release, thereby prolonging its mildew-proof effect, effectively preventing the regeneration of mold, and has the advantages of environmental protection and durability;
[0029] 3. The glass-based silver-zinc composite antibacterial agent of the present invention uses borate, borosilicate or phosphate glass as a carrier, and achieves antibacterial effect by slowly releasing silver ions and zinc ions, and has the characteristics of precise control of loading amount, adjustable ion release rate, stable and lasting release rate, etc. The composite metal ion antibacterial agent has stronger synergistic antibacterial effect and broad-spectrum antibacterial property. At the same time, the zinc ions in the silver-zinc ion composite antibacterial agent are conducive to stabilizing the existence of silver in the form of ions, overcoming the problem that a single silver ion antibacterial agent is easily oxidized to produce discoloration, which is conducive to improving the anti-discoloration performance of the antibacterial agent and increasing the weathering and discoloration resistance of the resin.
[0030] 4. The preparation method of the antibacterial and mildew-proof glue prepared by the present invention is simple to operate, easy to control, and suitable for industrial promotion and application.
[0031] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present invention. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the reactions are carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0033] Preparation Example
[0034] Preparation Example 1
[0035] A method for preparing an organic-inorganic composite emulsion comprises the following steps:
[0036] (1) 30g nano-SiO 2 , 40g of ethanol and 10g of aqueous solution were mixed and stirred evenly to obtain nano-SiO 2 Suspension;
[0037] (2) Add 6% by mass of silane coupling agent KH-550 to the nano-SiO 2 The suspension was heated to 70 °C and stirred for 4 h. After centrifugation, washing and drying, the modified nano-SiO 2 ;
[0038] (3) Mix the epoxy resin and the active diluent and stir evenly. The mass ratio of epoxy resin to active diluent is 4:1. Weigh 100 mL of the diluted epoxy resin and slowly add it to the modified nano-SiO 2 The suspension was stirred at 8000 r / min for 30 min to obtain a composite emulsion.
[0039] Preparation Example 2
[0040] A modified silica sol is a water dispersion of surface-modified nano silicon dioxide; the particle size of the modified silica sol is 10nm, the pH value is 8.0, and the mass content of non-volatile matter is 25%.
[0041] Preparation Example 3
[0042] A nano slow-release mildew preventer comprises quaternary ammonium salts, organosilicon quaternary ammonium salts, guanidines, halogenated amine compounds, nano titanium dioxide and nano zinc oxide. The quaternary ammonium salts, organosilicon quaternary ammonium salts, guanidines, halogenated amine compounds, nano titanium dioxide and nano zinc oxide are mixed in a mass ratio of 32:10:3:7:3:5.
[0043] Example
[0044] Example 1
[0045] An antibacterial and mildew-proof glue comprises the following components by weight: 15 parts of the organic-inorganic composite emulsion prepared in Preparation Example 1, 8 parts of the modified silica sol prepared in Preparation Example 2, 12 parts of a glass-based silver-zinc composite antibacterial agent, 0.6 parts of a nano slow-release mildew-proof agent prepared in Preparation Example 3, 0.01 parts of a catalyst, 22 parts of octyl isothiazolinone, 10 parts of diisocyanate, and 5 parts of a hyperbranched polyamine.
[0046] A method for preparing an antibacterial and mildew-proof adhesive comprises the following steps:
[0047] (1) The organic-inorganic composite emulsion prepared in Preparation Example 1, the modified silica sol prepared in Preparation Example 2, octyl isothiazolinone, diisocyanate and hyperbranched polyamine were mixed uniformly to prepare a composition A;
[0048] (2) Mixing the glass-based silver-zinc composite antibacterial agent, the nano slow-release mildew-proof agent prepared in Preparation Example 3, and a catalyst to prepare a composition B, wherein the catalyst is dibutyltin dilaurate;
[0049] (3) Mixing the composition A and the composition B and stirring them evenly to prepare an antibacterial and mildew-proof adhesive.
[0050] Example 2
[0051] An antibacterial and mildew-proof adhesive comprises the following components by weight: 16 parts of the organic-inorganic composite emulsion prepared in Preparation Example 1, 10 parts of the modified silica sol prepared in Preparation Example 2, 15 parts of a glass-based silver-zinc composite antibacterial agent, 0.8 parts of a nano slow-release mildew-proof agent prepared in Preparation Example 3, 0.05 parts of a catalyst, 28 parts of octyl isothiazolinone, 12 parts of diisocyanate, and 8 parts of a hyperbranched polyamine.
[0052] A method for preparing an antibacterial and mildew-proof adhesive comprises the following steps:
[0053] (1) The organic-inorganic composite emulsion prepared in Preparation Example 1, the modified silica sol prepared in Preparation Example 2, octyl isothiazolinone, diisocyanate and hyperbranched polyamine were mixed uniformly to prepare a composition A;
[0054] (2) Mixing the glass-based silver-zinc composite antibacterial agent, the nano slow-release mildew-proof agent prepared in Preparation Example 3, and a catalyst to prepare a composition B, wherein the catalyst is dibutyltin dilaurate;
[0055] (3) Mixing the composition A and the composition B and stirring them evenly to prepare an antibacterial and mildew-proof adhesive.
[0056] Example 3
[0057] An antibacterial and mildew-proof glue comprises the following components by weight: 18 parts of the organic-inorganic composite emulsion prepared in Preparation Example 1, 12 parts of the modified silica sol prepared in Preparation Example 2, 18 parts of a glass-based silver-zinc composite antibacterial agent, 1.2 parts of a nano slow-release mildew-proof agent prepared in Preparation Example 3, 0.8 parts of a catalyst, 31 parts of octyl isothiazolinone, 16 parts of diisocyanate, and 8 parts of a hyperbranched polyamine.
[0058] A method for preparing an antibacterial and mildew-proof adhesive comprises the following steps:
[0059] (1) The organic-inorganic composite emulsion prepared in Preparation Example 1, the modified silica sol prepared in Preparation Example 2, octyl isothiazolinone, diisocyanate and hyperbranched polyamine were mixed uniformly to prepare a composition A;
[0060] (2) Mixing the glass-based silver-zinc composite antibacterial agent, the nano slow-release mildew-proof agent prepared in Preparation Example 3, and a catalyst to prepare a composition B, wherein the catalyst is dibutyltin dilaurate;
[0061] (3) Mixing the composition A and the composition B and stirring them evenly to prepare an antibacterial and mildew-proof adhesive.
[0062] Example 4
[0063] An antibacterial and mildew-proof glue comprises the following components by weight: 20 parts of the organic-inorganic composite emulsion prepared in Preparation Example 1, 12 parts of the modified silica sol prepared in Preparation Example 2, 25 parts of a glass-based silver-zinc composite antibacterial agent, 2 parts of a nano slow-release mildew-proof agent prepared in Preparation Example 3, 2 parts of a catalyst, 40 parts of octyl isothiazolinone, 20 parts of a diisocyanate, and 15 parts of a hyperbranched polyamine.
[0064] A method for preparing an antibacterial and mildew-proof adhesive comprises the following steps:
[0065] (1) The organic-inorganic composite emulsion prepared in Preparation Example 1, the modified silica sol prepared in Preparation Example 2, octyl isothiazolinone, diisocyanate and hyperbranched polyamine were mixed uniformly to prepare a composition A;
[0066] (2) Mixing the glass-based silver-zinc composite antibacterial agent, the nano slow-release mildew-proof agent prepared in Preparation Example 3, and a catalyst to prepare a composition B, wherein the catalyst is dibutyltin dilaurate;
[0067] (3) Mixing the composition A and the composition B and stirring them evenly to prepare an antibacterial and mildew-proof adhesive.
[0068] Comparative Example
[0069] Comparative Example 1
[0070] The antibacterial and mildew-proof adhesive was prepared according to the method of Example 3, except that no organic-inorganic composite emulsion was added.
[0071] Comparative Example 2
[0072] The antibacterial and mildew-proof adhesive prepared according to the method of Example 3 is different in that no slow-release mildew-proof agent is added.
[0073] Comparative Example 3
[0074] The antibacterial and mildew-proof adhesive was prepared according to the method of Example 3, except that no modified silica sol was added.
[0075] Comparative Example 4
[0076] The antibacterial and mildew-proof adhesive prepared according to the method of Example 3 is different in that no glass-based silver-zinc composite antibacterial agent is added.
[0077] The antibacterial and mildew-proof adhesives in Examples 1-4 and Comparative Examples 1-4 were tested accordingly, and the test results are as follows:
[0078] (1) The surface drying time shall be tested in accordance with GB / T 13477;
[0079] (2) Anti-mildew performance test: The polyvinyl alcohol adhesive prepared in Examples 1-5 and Comparative Examples 1-3 was uniformly sprayed on the core paper of the corrugated paper, and dried at 100° C. to obtain the corrugated paperboard. According to the requirements of GB / T 4768-2008 "Anti-mildew packaging", the anti-mildew performance test was carried out. The blank control group paperboard and the anti-mildew paperboard were placed in a culture dish containing a mold culture medium, and a mold spore suspension was sprayed on each culture dish, wherein the mold was Aspergillus niger and the suspension concentration was 10 5 -10 7 / mL, treated in the mold test box for 28 days, observed the degree of mold growth, and then took samples to observe and record the mold resistance level. The mold resistance level classification standard is: no mold growth, level 0; mold growth area <10%, level Ⅰ; mold growth area 10-30%, level Ⅱ; mold growth area 30-60%, level Ⅲ; mold growth area >60%, level Ⅳ. Each group was tested three times and the average value was taken.
[0080] Table 1 Performance test of embodiments and comparative examples
[0081]
[0082]
[0083] As can be seen from Table 1, the performance of the antibacterial and mildew-proof adhesive prepared in Example 3 is better, while the performance of Comparative Example 1 is worse, which shows that the addition of nanoparticles in the organic-inorganic composite emulsion plays the role of stress concentration points. When subjected to external forces, the nanoparticles will deform, thereby changing the physical structure of the adhesive, enhancing its tensile strength and corrosion resistance, and making the antibacterial and mildew-proof adhesive more stable.
[0084] The above is only an exemplary embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. An antibacterial and mildew-proof adhesive, characterized in that: The invention comprises the following components by weight: 15-20 parts of organic-inorganic composite emulsion, 8-12 parts of modified silica sol, 12-25 parts of glass-based silver-zinc composite antibacterial agent, 0.6-2 parts of nano slow-release mildew preventer, 0.01-2 parts of catalyst, 22-40 parts of octyl isothiazolinone, 10-20 parts of diisocyanate and 5-15 parts of hyperbranched polyamine.
2. The antibacterial and mildew-proof adhesive according to claim 1, characterized in that: The invention comprises the following components by weight: 18-20 parts of organic-inorganic composite emulsion, 10-12 parts of modified silica sol, 15-20 parts of glass-based silver-zinc composite antibacterial agent, 0.6-1.5 parts of nano slow-release mildew preventer, 0.5-2 parts of catalyst, 22-32 parts of octyl isothiazolinone, 10-15 parts of diisocyanate and 10-15 parts of hyperbranched polyamine.
3. The antibacterial and mildew-proof adhesive according to claim 1, characterized in that: The organic-inorganic composite emulsion comprises a silane coupling agent, an active diluent, modified nano-SiO2 and an epoxy resin. The organic-inorganic composite emulsion is prepared by emulsifying the epoxy resin and the active diluent with the modified nano-SiO2.
4. The antibacterial and mildew-proof adhesive according to claim 1, characterized in that: The method for preparing the organic-inorganic composite emulsion comprises the following steps: (1) mixing nano-SiO2, ethanol and aqueous solution and stirring them uniformly to obtain a nano-SiO2 suspension; (2) adding silane coupling agents to the nano-SiO2 suspension respectively, heating and stirring, centrifuging, washing and drying to obtain modified nano-SiO2; (3) Mix the epoxy resin and the active diluent and stir evenly, weigh the diluted epoxy resin and slowly add it into the modified nano-SiO2 suspension, and stir at 6000-8000 r / min for 30-50 min to obtain a composite emulsion.
5. The antibacterial and mildew-proof adhesive according to claim 4, characterized in that: In the step (3), the mass ratio of the epoxy resin to the reactive diluent is 1-4:1-3.
6. The antibacterial and mildew-proof adhesive according to claim 1, characterized in that: The modified silica sol is a water dispersion of surface-modified nano silicon dioxide; the particle size of the modified silica sol is 5-12 nm, the pH is 8.0-10.0, and the mass content of non-volatile matter is 25-30%.
7. The antibacterial and mildew-proof adhesive according to claim 1, characterized in that: The nano slow-release mildew preventer comprises quaternary ammonium salts, organosilicon quaternary ammonium salts, guanidines, halogenated amine compounds, nano titanium dioxide and nano zinc oxide, and the mass ratio of the quaternary ammonium salts, organosilicon quaternary ammonium salts, guanidines, halogenated amine compounds, nano titanium dioxide and nano zinc oxide is 32-42:10-12:2-3:5-12:1-3:5-8.
8. The antibacterial and mildew-proof adhesive according to claim 1, characterized in that: The catalyst is at least one of dibutyltin dilaurate, dibutyltin diacetate, dibutyltin dioctoate and a titanium chelate.
9. The method for preparing the antibacterial and mildew-proof adhesive according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) uniformly mixing an organic-inorganic composite emulsion, a modified silica sol, octyl isothiazolinone, a diisocyanate and a hyperbranched polyamine to prepare a composition A; (2) mixing a glass-based silver-zinc composite antibacterial agent, a nano slow-release mildew-proof agent and a catalyst to prepare a composition B; (3) Mixing the composition A and the composition B and stirring them evenly to prepare an antibacterial and mildew-proof adhesive.
10. Use of the antibacterial and mildew-proof adhesive prepared according to claim 1 or claim 9 in building interior materials.
Citation Information
Patent Citations
Nano modified epoxy resin floor coating and preparation method thereof
CN109486345A
Modified nanoparticle suspension as well as preparation method and application thereof
CN109908767A
Preparation method and application of two-component anticorrosive antibacterial adhesive
CN118185531A
Cited By
Efficient mildew-proof coating and processing technology thereof
CN120349681A